Association between HALP score and clinical outcome in patients with aneurysmal subarachnoid hemorrhage: insights from a large cohort study - Yang, Jun; Zhu, Bingcheng; Zhao, Jizong; Chen, Xiaolin (Frontiers in Neurology, 2025)
BackgroundThe HALP (hemoglobin, albumin, lymphocyte, and platelet) score is a newly emerging index for reflecting the systemic inflammation and nutritional status of patients. Previous studies have identified that HALP score is associated with clinical outcomes of various diseases. This study aims to explore the relationship between HALP score and clinical outcomes in patients with aneurysmal subarachnoid hemorrhage (aSAH).MethodsA total of 748 aSAH patients were included in this study. Patients were divided into tertiles based on their HALP score levels. At 90 days after discharge, patients received follow up and the modified Rankin Scale (mRS) was used to assess the functional outcome. Unfavorable functional outcome was defined as mRS ≥ 3. Multivariate logistic regression for poor functional outcome and postoperative complications was performed to explore the association between HALP score and clinical outcomes of aSAH patients, with adjustment for age, sex, and other important factors.ResultsCompared to patients with a high HALP score, patients with a low HALP score tended to be female, had a higher Hunt Hess score, and had higher levels of glucose and creatine. After adjusting several potential confounding factors, multivariate logistic regression showed that patients with a low HALP score had a higher risk of unfavorable functional outcome (OR, 0.095, 95%CI: 0.056–0.163, p < 0.001). The receiver operating curve (ROC) analysis demonstrated that the area under the curve (AUC) was 0.795. Furthermore, multivariate logistic regression also demonstrated that low HALP score might increase the risk of postoperative pneumonia (OR, 0.586, 95%CI: 0.388–0.887, p = 0.012).ConclusionGiven that HALP score may contribute to identify aSAH patients at high risk for poor prognosis, these findings hold significant clinical relevance.